Enhancing user experience in online learning environments: Design, evaluation, and usability techniques - Yaw Ofosu-Asare (Journal of Graphic Engineering and Design)
This study aims to enhance user experience on online learning platforms by investigating design principles, usability evaluation techniques, and redesign processes. A total of 150 participants, divided equally among students, educators, and professionals, were stratified by age, gender, education level, and familiarity with online learning. Various evaluation methods, including heuristic evaluation, guideline reviews, and cognitive walkthroughs, were employed. Metrics such as task success rate, time-on-task, and Net Promoter Score (NPS) were used to quantify user satisfaction and effectiveness. Additionally, five qualitative interviews were conducted for deeper insights. The results revealed specific usability issues and demonstrated the effectiveness of the applied evaluation techniques. Post-redesign metrics indicated significant improvements in user satisfaction and engagement. The study underscores the importance of a multi-faceted approach to design and evaluation in online learning platforms and suggests avenues for future research.